Value of Exome Sequencing in Diagnosis and Management of Recurrent Non-immune Hydrops Fetalis: A Retrospective Analysis - Zhou, Xinyao; Zhou, Jia; Wei, Xing; Yao, Ruen; Yang, Yingjun; Deng, Linbei; Zou, Gang; Wang, Xietong; Yang, Yaping; Duan, Tao; Wang, Jian; Sun, Luming (Frontiers in Genetics, 2021)
The purpose of the study was to use exome sequencing (ES) to study the contribution of single gene disorders to recurrent nonimmune hydrops fetalis (NIHF) and retrospectively evaluate the value of genetic diagnosis on prenatal management and pregnancy outcome. From January 2012 to October 2018, a cohort of twenty-eighty fetuses with recurrent NIHF were analyzed by trio ES. Fetuses with immune hydrops, nongenetic factors (including infection et al.), karyotype or CNV abnormalities were excluded. Variants were interpreted based on ACMG/AMP guidelines. Fetal therapy was performed on seven fetuses. Of the 28 fetuses, 10 (36%) were found to carry causal genetic variants (pathogenic or likely pathogenic) in 8 genes (GBA, GUSB, GBE1, RAPSN, FOXC2, PIEZO1, LZTR1, and FOXP3). Five (18%) fetuses had variant(s) of uncertain significance (VUS). Of the 10 fetuses with definitive molecular diagnosis, five (50%) were diagnosed with inborn errors of metabolism. Among the seven fetuses received fetal therapy, two had definitive molecular diagnosis and resulted in neonatal death. Among the remaining five fetuses with negative results, four had newborn survival and one had intrauterine fetal death. Trio ES could facilitate genetic diagnosis of recurrent NIHF and improve the prenatal management and pregnancy outcome.